A numerical method for studying the effect of calcium silicate lining on road tunnel fires. (1st March 2022) - Tomar, Mukesh Singh; Khurana, Shashank; Chowdhury, Snehaunshu
Highlights: Numerical simulation of road tunnel fire using pyrolysis is performed. Effect of a structural linings (calcium silicate) on tunnel fire is discussed. Influence of calcium silicate linings on peak HRR is studied. Influence of calcium silicate linings on tunnel temperature is studied. Importance of peak HRR in tunnel fire is highlighted. Abstract: Road tunnel fires can jeopardize the life safety of occupants and the structural integrity of the tunnel. Such fires are usually characterized by the heat release rate (HRR) parameter. Most tunnel fire safety systems are designed based on this parameter. The tunnel structure (walls and ceilings) are usually protected with a passive protections such as magnesium oxide boards, cementitious sprays, polypropylene fiber mix or calcium silicate boards. Amongst these materials, calcium silicate boards are the most popular choice due to their easy installation and capability to protect the tunnel at very high temperatures for several hours. The HRR in a tunnel fire depends on various parameters such as type of vehicle involved in the fire, amount of fuel, location of fuel and ignition source, tunnel geometry, presence of fixed firefighting systems/ventilation, and several other factors. However, no evidence of structural linings (passive protection) affecting the heat release rate is found in the literature. To investigate the role of structural linings (calcium silicate) on the HRR, a numerical study using Fire Dynamic Simulator (FDS) is conducted for a road tunnel involving fire in a heavy goods vehicle. Two scenarios are investigated; one considering concrete tunnel linings without any passive protection while in the second scenario the tunnel is protected with calcium silicate linings. Comparison of the results from the two abovementioned scenarios reveal different patterns of HRR and tunnel temperatures and suggests that in large fires, structural linings such as calcium silicate lining can alter the overall HRR by enhancing the heat feedback and fuel burning rates inside the tunnel.